Direct synthesis of few- and multi-layer graphene films on dielectric substrates by "etching-precipitation" method. (February 2015) - Kosaka, Masaki; Takano, Soichiro; Hasegawa, Kei; Noda, Suguru
Abstract: A novel "etching-precipitation" method is proposed and developed for the direct synthesis of graphene on dielectric substrates. In this method, graphene precipitates from the Fe–C solid solution film during selective etching of Fe using Cl2 gas. Few- and multi-layer graphene is fabricated directly on quartz glass and SiO2 /Si substrates without Fe residue at a growth temperature of 500–650 °C, which is a significantly lower temperature than used in the conventional chemical vapor deposition method. The 6- to 7-layer graphene synthesized at 650 °C shows a volume resistivity of 80–140 μΩ cm. The average number of layers can be easily controlled in a linear fashion with the initial carbon feed, which is proportional to the thickness of the starting Fe–C films. Line-patterned multi-layer graphene is also fabricated by simply pre-patterning the starting Fe–C film although its structure is somewhat different from typical graphene ribbons. "Etching-precipitation" will be a practical route to synthesize graphene with micro-patterns directly onto device substrates of arbitrary sizes.